Exploring the Compatibility of Islamic Foundations with International Humanitarian Law - Mahmuluddin; Asyidiqi, Hasbi (CV Global Research Publication, 2024)
This research explores the historical evolution and contemporary significance of Islamic principles in international humanitarian law. Through a comparative literature analysis, the study uncovers the contributions of early Islamic practices and scholars to the development of modern humanitarian norms. The findings demonstrate the compatibility of Islamic values with contemporary legal frameworks, while also addressing challenges posed by diverse cultural interpretations. Additionally, the study emphasizes the active role of Islamic organizations in promoting humanitarian ethics in the present era. These insights provide a foundation for fostering inclusive approaches and integrating Islamic principles into global humanitarian discussions.